Effectiveness of Endoscopic Sclerotherapy with Aluminum Potassium Sulfate and Tannic Acid as a Non-Surgical Treatment for Internal Hemorrhoids - Yuichi Tomiki; Jun Aoki; Shunsuke Motegi; Rina Takahashi; Toshiaki Hagiwara; Yu Okazawa; Kosuke Mizukoshi; Masaya Kawai; Shinya Munakata; Shun Ishiyama; Kiichi Sugimoto; Kazuhiro Sakamoto (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims Sclerotherapy with aluminum potassium sulfate and tannic acid (ALTA) has a potent effect on internal hemorrhoids. In this retrospective study, we compared the effects of endoscopic ALTA therapy and standard ALTA therapy. Methods We investigated patients who underwent treatment for internal hemorrhoids at our institution between 2014 and 2016. They were divided into a standard ALTA group (n=33, treated using proctoscopy) and an endoscopic ALTA group (n=48). We compared the clinical findings between the 2 groups. Results There were no intergroup differences in background factors. The mean ALTA dose was 21.9±7.2 mL and 17.8±3.4 mL in the standard and endoscopic ALTA groups, respectively (p<0.01). Adverse events occurred in 4 patients (12.1%) from the standard ALTA group and 6 patients (12.5%) from the endoscopic ALTA group. In both groups, the patients reported good satisfaction with the therapeutic effect at 1 month after the procedure. Hemorrhoids recurred in 2 patients (6.3%) from the standard ALTA group and 4 patients (8.3%) from the endoscopic ALTA group. Conclusions Endoscopic ALTA sclerotherapy is equivalent to standard ALTA therapy in terms of efficacy, adverse events, and recurrence. Therefore, it is a useful non-surgical option for patients with internal hemorrhoids who prefer a less invasive treatment.